Compendium of Technologies for Higher Yield and Aflatoxin Management in Groundnut - Issah Sugri; Osei-Agyeman Yeboah; John K. Bidzakin; Salim Lamini; Rashidatu Abdulai; Ahmed Seidu; Jerry Asalma Nboyine; Mukhtaru Zakaria; Mutari Abubakari; Issah Alidu Abukari; et al. (Current Research Progress in Agricultural Sciences Vol. 7, 2025)
In Ghana, groundnut (Arachis hypogaea L.) production plays an important role in livelihoods; particularly for women farmers in rural communities. Per capita consumption is estimated at 12 kg per year. About 80% of Ghanaians consume groundnut products at least once a week, and about 32% at least thrice a week. About 39% of consumers in Northern Ghana grow it themselves. Three salient challenges limiting groundnut production are low access to improved seed, poor soils, and aflatoxin contamination. This study adopted integrated strategies to enhance the knowledge of actors on best production technologies to increase yield and reduce the risk of aflatoxin contamination. In this study, on-farm validation trials were conducted to provide a platform to showcase the effects of best practices (i.e. improved variety, soil amendments, Rhizobium inoculants, and integrated pest management) on yield and aflatoxin contamination. The average yield of the farmers’ practice was 0.56 to 0.95 t/ha compared to 0.85 to 1.26 t/ha from best management practices. The pod yield of the integrated pest management plots (1.03 t/ha) outperformed the farmer practice (0.64 t/ha) across the locations. The application of organic manure, mineral fertilizer, and manure + mineral fertilizer increased yield by 23.5%, 30%, and 39%, respectively, over the control. The application of YARA-Legume + Rhizobium inoculant or TSP + Rhizobium inoculant resulted in consistently higher pod yield (1.22 t/ha) and (1.01 t/ha), respectively compared to the control (0.57 t/ha), or single application of any amendment. At 12 ppm permissible level, all samples contained safe aflatoxin levels (4.43 to 5.45 ppm) at 8 months after harvest. In conclusion, a significant reduction in aflatoxins contamination can be achieved by integrating these practices into the current groundnut production systems. Albeit, access (cost and availability) to these technologies remains a barrier to disseminating these technologies to largely smallholder farmers.